The Implementation of Indonesia’s Blue Economy as a Global Role Strengthening in ASEAN Region - Sidney Mayra Aquila Gerungan; Triesanto Romulo Simanjuntak; Petsy Jessy Ismoyo (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This article explores Indonesia’s Blue Economy implementation as a strategic effort to strengthen its maritime identity and global standing in the ASEAN region. The study focuses on the role of the Ministry of Marine Affairs and Fisheries (KKP) from 2022 to 2024 in promoting sustainable ocean development. Utilizing a descriptive qualitative method and grounded in classical liberalism theory, the research highlights the government’s responsibility in fostering a transparent, cooperative, and rules-based international maritime environment. One of the key initiatives analyzed is the 2022 Focus Group Discussion (FGD), which facilitated multi-stakeholder participation in the formulation of long-term aquaculture policies. These policies emphasize sustainability, institutional resilience, and community engagement. The FGD is seen as a platform for inclusive governance, where various actors contribute to building a more adaptive and sustainable maritime economy. The article also highlights the Kampung Nelayan Modern program in Papua as a concrete example of integrated community-based development. This program has resulted in improved productivity, access to facilities, and the overall welfare of coastal communities, showing how targeted investment can uplift marginalized regions. Additionally, the Ocean Big Data system is presented as a transformative tool in marine governance. This system enhances the ability of policymakers to make real-time, data-driven decisions, thereby improving monitoring, enforcement, and sustainable use of marine resources. Findings suggest that Indonesia’s Blue Economy approach significantly strengthens national maritime resilience and serves as a model for regional maritime diplomacy. Through strategic programs and digital innovation, Indonesia demonstrates how a developing archipelagic country can leverage sustainability as a tool for both domestic development and international influence. By linking internal reforms with regional collaboration, Indonesia positions itself as a normative leader in ASEAN, advancing economic growth while preserving ocean health.